PEMECAHAN MASALAH OPTIMASI BERSIFAT PROBABILISTIK MENGGUNAKAN CHANGE-CONSTRAINED PROGRAMMING - Marpaung, Budi (Teknik dan Ilmu Komputer, 2013)
Change-Constrained Programming (CCP) is an optimization model developed to solve probabilistic problems. In real world, particularly in the industry, constrained coefficients and right-hand side constants cannot be firmly determined. This paper explains how the CCP is used to optimize the company profits by making various products using various machines that have limited capacity and are probabilistic. It was evident that CCP can succesfully provide an optimal solution. Keywords: Change-Constrained Programming, level of confidence, objective function coefficient, righ-hand-side, optimal